Enhancing wheat productivity and economics through microbe-mediated phosphorus fertilization in wheat (Triticum aestivum) + mustard (Brassica juncea) intercropping systems of the semi-arid region of India - KARAN, SHYAM; SINGH, Y V; KUMAR, AMIT; DASS, ANCHAL; KUMAR, SANDEEP (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during the winter (rabi) season of 2021–22 and 2022–23 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the impact of microbe-mediated phosphorus fertilization on the growth, yield attributes and yield of wheat (Triticum aestivum L.) in intercropping systems. Four cropping systems (CSs), viz. CS1, Sole wheat (control); CS2, Sole mustard (Brassica juncea); CS3, Wheat + mustard (5:1); CS4, Wheat + mustard (5:2) and six P management strategies (PMS) viz. PMS1, Control; PMS2, RDF; PMS3, 75% RDP + PSB (0.5 kg/ha); PMS4, 75%RDP + PROM (125 kg/ha); PMS5, 75% RDP + PROM (125 kg/ha) + PSB (0.5 kg/ha); PMS6, No RDP + PROM (125 kg/ha) + PSB (0.5 kg/ha) in a factorial randomized block design (FRBD) with three replications. Among the PMS; 75% RDP + PROM + PSB (PMS5) significantly outperformed others. It recorded the highest wheat equivalent yield (56.86 q/ha), which was 34.5% higher than the control (PMS1). This was accompanied by the highest 1000 grain weight (41.8 g), tillers no. (509.7/m²), harvest index (43.1%) and net return (₹129.3 ×10³/ha), with a benefit-cost ratio of 3.28 (vs. 2.76 in PMS1). Additionally, PMS5 improved dry matter accumulation at harvest (1001 g/m2, a 23.1% increase over PMS1), leaf area index (5.73), and crop growth rate (4.57 g/m²/day at 40 DAS, up by 37.3% over PMS1). In terms of cropping systems, CS4 (wheat + mustard in 5:2 row ratio) proved superior with the highest wheat equivalent yield (56.16 q/ha), representing a 9.6% increase over sole wheat (CS1). This system also enhanced dry matter accumulation (1000 g/m2), crop growth rate at 80 DAS (18.9 g/m²/day), and net returns (₹82.2×10³/ha), while maintaining a high benefit-cost ratio (2.44). These results underscore the potential of 75% RDP + PROM + PSB and strategic intercropping (wheat + mustard in 5:2 row ratio) with mustard for improving productivity and profitability and support the adoption of biologically enriched P sources to reduce dependency on chemical fertilisers.